Parents’ Use of Subsidiaries to “Push Down” Earnings Management: Evidence from Italy - Bonacchi, Massimiliano; Cipollini, Fabrizio; Zarowin, Paul (Contemporary Accounting Research, 2018)
Abstract We find evidence consistent with Italian nonlisted subsidiaries engaging in accrual and real earnings management, so that their listed parents can meet or beat benchmarks. Thus, the parent firm drives the earnings management of the subsidiaries. We identify parents that are more likely to have managed earnings as the ones that avoid a small loss or meet or beat analyst forecast by a few cents. Cross‐sectional analysis reveals that Big 4 auditors mitigate accrual earnings management at the subsidiary level and that family‐owned firms use earnings management through nonlisted subsidiaries mainly to avoid reporting losses. Finally, we find that parent firms communicate earnings management strategies to their subsidiaries using board proximity. Our evidence shows that business groups manage earnings differently from single firms, pushing earnings management down to subsidiaries. It also supports the monitoring role of Big 4 auditors in a business group setting and contributes to understanding financial reporting decisions in family‐owned firms.